2021
DOI: 10.51847/yaqc7knnoy
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas sp Isolated from Wastewater and their Interaction with Microalgae

Abstract: During biodegradation processes in Wastewater Treatment Plants (WWTP), bacteria play an important role, and associations of bacteria with microalgae have the potential to remediate wastewater by reducing pollutants. This work aimed to identify bacteria present in wastewater and to analyze their interaction with C. vulgaris to favor their phytoremediation. The physicochemical and microbiological characterization of the wastewater from the Alseseca-Sur WWTP was carried out, identifying the bacterial isolates, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Enoyl-CoAhydratase plays a role as a catalyst in the (R)-specific hydration of 2-enoyl-CoA which in turn supplies (R)-3-hydroxyacyl-CoA monomers for the synthesis of PHA by fatty acid β-oxidation pathway (Zhang et al, 2019). P.oleovorans, P. aeruginosa, Burkholderia caryophylli can synthesize mcl-PHAs while, R. eutropha is unable to do so (Pérez-Nava et al, 2021). These organisms accommodate two phaC genes which are split apart by a phaZ gene in the phaC1ZC2D operon.…”
Section: Genes and Enzymes Involved In Pha Synthesismentioning
confidence: 99%
“…Enoyl-CoAhydratase plays a role as a catalyst in the (R)-specific hydration of 2-enoyl-CoA which in turn supplies (R)-3-hydroxyacyl-CoA monomers for the synthesis of PHA by fatty acid β-oxidation pathway (Zhang et al, 2019). P.oleovorans, P. aeruginosa, Burkholderia caryophylli can synthesize mcl-PHAs while, R. eutropha is unable to do so (Pérez-Nava et al, 2021). These organisms accommodate two phaC genes which are split apart by a phaZ gene in the phaC1ZC2D operon.…”
Section: Genes and Enzymes Involved In Pha Synthesismentioning
confidence: 99%
“…The type of growth media greatly influences the efficiency of microalgae-bacteria interactions, impacting biomass production and nutrient removal efficiency. Pérez-Nava et al [ 115 ] demonstrated that C. vulgaris and Pseudomonas sp. have enhanced growth in wastewater compared to Bold's basal media, with microalga growth diminishing as the ratio of Bold's basal media increases.…”
Section: The Interaction Application and Optimization Of Microalgae-b...mentioning
confidence: 99%
“…The inhibition zones ranged from 7 to 24 mm, and all of the tested bacteria (K. pneumonia, E. coli, E. cloacae, S. aureus, S. epidermidis, Shigella sp., and P. aeruginosa) were susceptible to it to varied degrees (Table 1). These variations in the sensitivity of gram-positive and gram-negative bacteria to nanoparticles may result from these differences in the cell surfaces of these bacteria [22,23]. The activity of the AgNPs (such as antimicrobial efficacy) depends on their specific surface areas.…”
Section: Synergistic Effects Against Shigella Spmentioning
confidence: 99%